Effects of process variables on the strength properties of veneer laminated cement bonded particle board from mixed tropical hardwoods (1999)
Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) of veneer laminated wood cement panel were evaluated. The boards were made of 3 layers comprising 1.5 mm thick mixed hardwoods sawdust for the two surfaces, and 9mm thick core layer made of plantation grown Gmelina arboma flakes. Three variables were investigated namely: Density at three levels (1000 kg/m3, 1100kg/m3 and 1200 kg/m3), Cement wood ratios of 2.5:1.0, 2.75:1.0 and 3.0:1.0 and glue spread of 1.02 kg/m2, 1.43 kg/m2 and 1,74 kg/m2 double due line (DGL) for the boards lamination. For all the treatment combinations, the MOR ranged from 26.79 N/mm to 42.59 N/mm2 while for MOE, the mean value was in the range of 3114N/mm2 to 5310N/mm2. At board density level of 1250 kg/m3 the laminated panels gave value of the highest MOR and MOE. Statistical analysis showed that the three variables considered in this study had significant on the board strength.